A circulating extracellular vesicles‐based novel screening tool for colorectal cancer revealed by shotgun and data‐independent acquisition mass spectrometry. Issue 1 (14th April 2020) - Zheng, Xi; Xu, Kailun; Zhou, Biting; Chen, Ting; Huang, Yanqin; Li, Qilong; Wen, Fei; Ge, Weiting; Wang, Jian; Yu, Shaojun; Sun, Lifeng; Zhu, Liang; et al.
ABSTRACT: Background : Early screening for colorectal cancer (CRC) is essential to improve its prognosis. Liquid biopsies are increasingly being considered for diagnosing cancer due to low invasiveness and high reproducibility. In addition, circulating extracellular vesicles (crEVs, extracellular vesicles isolated from plasma) expressing tumour‐specific proteins are potential biomarkers for various cancers. Here, we present a data‐independent acquisition (DIA)‐mass spectrometry (MS)‐based diagnostic method for liquid biopsies. Methods : Extracellular vesicles (EVs) were isolated from culture supernatants of human CRC cell lines, and plasma of patients with CRC at different tumour stages, by overnight ultracentrifugation coupled with sucrose density gradient centrifugation. Tumour‐specific EV proteins were prioritized using Tandem Mass Tag (TMT)‐based shotgun proteomics and phosphoproteomics. The results were verified in a second independent cohort and a mouse tumour‐bearing model using Western blotting (WB). The candidate biomarkers were further validated in a third cohort by DIA‐MS. Finally, the DIA‐MS methodology was accelerated to permit high‐throughput detection of EV biomarkers in another independent cohort of patients with CRC and healthy controls. Results : High levels of total and phosphorylated fibronectin 1 (FN1) in crEVs, haptoglobin (HP), S100A9 and fibrinogen α chain (FGA) were significantly associated with cancer progression. FGA was the most dominant biomarker candidate. Analysis of the human CRC cell lines and the mouse model indicated that FGA+ crEVs were likely released by CRC cells. Furthermore, fast DIA‐MS and parallel reaction monitoring (PRM)‐MS both confirmed that FGA+ crEVs could distinguish colon adenoma with an area of curve (AUC) in the receiver operating characteristic (ROC) curve of 0.949 and patients with CRC (AUC of ROC is 1.000) from healthy individuals. The performance outperformed conventional tumour biomarkers. The DIA‐MS quantification of FGA+ crEVs among three groups agreed with that from PRM‐MS. Conclusion : DIA‐MS detection of FGA+ crEVs is a potential rapid and non‐invasive screening tool to identify early stage CRC. Abbreviations: FGA: fibrinogen α chain; CRC: colorectal cancer; crEVs: circulating extracellular vesicles; EV: extracellular vesicles;MS: mass spectrometry; WB: Western blotting; ROC: receiver operating characteristic; PRM: Parallel Reaction Monitoring; GPC1: Glypican‐1; GO: Gene ontology; TEM: transmission electron microscopy; FN1: Fibronectin 1; HP: haptoglobin; TMT: Tandem Mass Tag; LC‐MS/MS: liquid chromatography coupled to tandem mass spectrometry; DIA: data‐independent acquisition; DDA: data‐dependent acquisition; CiRT: Common internal Retention Time standards;AGC: Automatic gain control; AUC: area under curve.